Microarchitectural changes in the mandibles of ovariectomized rats: a systematic review and meta-analysis - Jeong-Hee Lee; Sang-Sun Han; Chena Lee; Young Hyun Kim; Bulgan Battulga (BMC, 2019)
Abstract Background This study aimed to examine radiologic microarchitectural changes in the mandibles of ovariectomized (OVX) rats through a systematic review and meta-analysis and to identify factors of the OVX rat model that influence on the bone microstructure. Methods Eligible articles were identified by searching electronic databases, including Embase, Medline, Web of Science, and KoreaMed, for articles published from January 1966 to November 2017. Two reviewers independently performed study selection, data extraction, and quality assessment. The pooled standardized mean difference (SMD) with 95% confidence intervals was calculated using a random-effects model. Subgroup analysis and meta-regression were performed to explore the effect of potential sources on the outcomes. The reliability of the results was assessed by sensitivity analysis and publication bias. Results Of 1160 studies, 16 studies (120 OVX and 120 control rats) were included in the meta-analysis. Compared to the control group, the OVX rats' trabecular bone volume fraction (SMD = − 2.41, P < 0.01, I2 = 81%), trabecular thickness (SMD = − 1.73, P < 0.01, I2 = 73%) and bone mineral density (SMD = − 0.95, P = 0.01, I2 = 71%) displayed the bone loss consistent with osteoporosis. The trabecular separation (SMD = 1.66, P < 0.01, I2 = 51%) has widen in the OVX mandibular bone in comparison to the control group. However, the trabecular number showed no indication to detect the osteoporosis (SMD = − 0.45, P = 0.38, I2 = 76%). The meta-regression indicated that longer post-OVX periods led to greater changes in bone mineral density (β = − 0.104, P = 0.017). However, the rats' age at OVX was not linked to bone microstructure change. Conclusions Using meta-regression and sensitivity analysis techniques, heterogeneity across the micro CT studies of OVX-induced osteoporosis was found. The major factors of heterogeneity were the region of interest and post-OVX period. Our assessment can assist in designing experiments to maximize the usefulness of OVX rat model.